2017
DOI: 10.3389/fmed.2017.00073
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovering Beta-2 Microglobulin As a Biomarker across the Spectrum of Kidney Diseases

Abstract: There is currently an unmet need for better biomarkers across the spectrum of renal diseases. In this paper, we revisit the role of beta-2 microglobulin (β2M) as a biomarker in patients with chronic kidney disease and end-stage renal disease. Prior to reviewing the numerous clinical studies in the area, we describe the basic biology of β2M, focusing in particular on its role in maintaining the serum albumin levels and reclaiming the albumin in tubular fluid through the actions of the neonatal Fc receptor. Diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
209
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(238 citation statements)
references
References 318 publications
5
209
0
4
Order By: Relevance
“…Serum beta‐2 microglobulin is independent from muscle mass, and the production of this protein is increased during infection and inflammatory processes . Recent research showed that serum beta‐2 microglobulin to assess glomerular filtration function might be less favorable in pediatric populations as compared to adults . However, urinary beta‐2 microglobulin might be more useful since beta‐2 microglobulin is removed from the serum by glomerular filtration, but almost all of the filtered protein is reabsorbed in the proximal tubule.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum beta‐2 microglobulin is independent from muscle mass, and the production of this protein is increased during infection and inflammatory processes . Recent research showed that serum beta‐2 microglobulin to assess glomerular filtration function might be less favorable in pediatric populations as compared to adults . However, urinary beta‐2 microglobulin might be more useful since beta‐2 microglobulin is removed from the serum by glomerular filtration, but almost all of the filtered protein is reabsorbed in the proximal tubule.…”
Section: Resultsmentioning
confidence: 99%
“…31 Recent research showed that serum beta-2 microglobulin to assess glomerular filtration function might be less favorable in pediatric populations as compared to adults. 38 However, urinary beta-2 microglobulin might be more useful since beta-2 microglobulin is removed from the serum by glomerular filtration, but almost all of the filtered protein is reabsorbed in the proximal tubule. This results in a minimal urinary beta-2 microglobulin concentration.…”
Section: Exploratory Data Analysis Of Age-dependent Changesmentioning
confidence: 99%
“…26,27 Recent studies discovered that β 2 M is not only a biomarker in patients with chronic kidney disease and endstagerenaldisease,butalsoapromisingmarkertoassessglomerular and tubular function in adults. 28 However, our study first found the role of β 2 M in the reversal of renal failure and recovery from dialysis dependence.…”
Section: Discussionmentioning
confidence: 66%
“…All four fingerprint proteins of the LS population are functionally important during inflammation, suggesting that an inflammatory response is activated in gill tissue of the LS population. Caspase 1 (G3P6H8) is part of the inflammsome complex 11 , beta-2-microglobulin (G3Q6I1) is a common inflammatory protein that has been used as a biomarker of inflammation associated with human diseases 12 , metalloendopeptidases (inlc. choryolysin L-type, G3PN26) are potant targets of anti-inflammatory drugs 13 , and sphingomyelin phosphodiesterases (incl.…”
Section: /20mentioning
confidence: 99%